Convergence of fungal traits over time in natural and forestry-fragmented patches. (November 2020) - Dawson, Samantha K.; Berglund, Håkan; Ovaskainen, Otso; Snäll, Tord; Jonsson, Bengt G.; Jönsson, Mari
Abstract: Setting aside small remnant patches of high biodiversity forest within managed forest landscapes is often used as conservation measure to provide a refuge and future source population of forest biodiversity, including wood-inhabiting fungal communities. Yet little is known about the long-term fungal community assembly, how these small, isolated patches change through time and how forest management in the surrounding landscape impacts traits and community functionality housed within. We applied a joint species distribution model to compare how fungal traits and communities changed over two survey periods undertaken 20 years apart in boreal forest set-aside and natural patches. Natural patches in naturally fragmented landscapes were considered reference forests for small, remnant, near-natural forest patches in intensively managed forest landscapes. We found the majority of fungal traits converged over time between set-aside and natural patches, without changes in overall species richness. Red-listed species occurrence was initially lower in set-aside patches, but reached a comparable level of natural patches over time as a result of opposing changes in both patch types. Functional trait changes were larger in set-aside patches, but convergence was also related to opposing changes in natural patches. This is the first study to directly measure and test wood fungal community trait-environment relationships over time in small, high-conservation value forest patches. The long-term functional trait and red-listed species values of set-asides, coupled with their capacity for old-growth recovery, make them valuable focal areas for conservation.